Identification of species-specific nuclear insertions of mitochondrial DNA (numts) in gorillas and their potential as population genetic markers (2014)
ABSTRACT: The first hyper-variable region (HV1) of the mitochondrial control region (MCR) has been widely used as a molecular tool in population genetics, but inadvertent amplification of nuclear translocated copies of mitochondrial DNA (numts) in gorillas has compromised the use of mitochondrial DNA in population genetic studies. At least three putative classes (I, II, III) of gorilla-specific HV1 MCR numts have been uncovered over the past decade. However, the number, size and location of numt loci in gorillas and other apes are completely unknown. Furthermore, little work to date has assessed the utility of numts as candidate population genetic markers. In the present study, we screened Bacterial Artificial Chromosome (BAC) genomic libraries in the chimpanzee and gorilla to compare patterns of mitochondrial-wide insertion in both taxa. We conducted an intensive BLAST search for numts in the gorilla genome and compared the prevalence of numt loci originating from the MCR with other great ape taxa. Additional gorilla specific MCR numts were retrieved either through BAC library screens or using an anchored-PCR (A-PCR) amplification using genomic DNA from five unrelated gorillas. Locus-specific primers were designed to identify numt insertional polymorphisms and evaluate their potential as population genetic markers. Mitochondrial-wide surveys of chimpanzee and gorilla BACs showed that the number of numts does not differ between these two taxa. However, MCR numts are more abundant in chimpanzees than in other great apes. We identified and mapped 67 putative gorilla- specific numts, including two that contain the entire HV1 domain, cluster with sequences from two numt classes (I, IIb) and will likely co-amplify with mitochondrial sequences using most published HV1 primers. However, phylogenetic analysis coupled with post-hoc analysis of mitochondrial variation can successfully differentiate nuclear sequences. Insertional polymorphisms were evident in three out of five numts examined, indicating their potential utility as molecular markers. Taken together, these findings demonstrate the potentially powerful insight that numts could make in uncovering population history in gorillas and other mammals.